Angular for Enterprise-Ready Web Applications - Second Edition - Uluca, Doguhan (Packt Publishing, 2020)
Revised and updated second edition of the bestselling hands-on guide to building enterprise-ready web apps using an evergreen Angular platform Key Features Updated examples, projects, and a new overview of tools - including NgRX and Ivy, automated testing, and Firebase authentication New chapter summarizing history of web frameworks and Angular version updates All-new RESTful API implementation leveraging the MEAN stack with MongoDB, Express.js, Angular and Node.js Book Description This second edition of Angular for Enterprise-Ready Web Applications is updated with in-depth coverage of the evergreen Angular platform. You'll start by mastering Angular programming fundamentals. Using the Kanban method and GitHub tools, you'll build great-looking apps with Angular Material and also leverage reactive programming patterns with RxJS, discover the flux pattern with NgRx, become familiar with automated testing, utilize continuous integration using CircleCI, and deploy your app to the cloud using Vercel Now and GCloud. You will then learn how to design and develop line-of-business apps using router-first architecture with observable data anchors, demonstrated through oft-used recipes like master/detail views, and data tables with pagination and forms. Next, you'll discover robust authentication and authorization design demonstrated via integration with Firebase, API documentation using Swagger, and API implementation using the MEAN stack. Finally, you will learn about DevOps using Docker, build a highly available cloud infrastructure on AWS, capture user behavior with Google Analytics, and perform load testing. By the end of the book, you'll be familiar with the entire gamut of modern web development and full-stack architecture, learning patterns and practices to be successful as an individual developer on the web or as a team in the enterprise. What you will learn Adopt a minimalist, value-first approach to delivering web apps Master Angular development fundamentals, RxJS, CLI tools, GitHub, and Docker Discover the flux pattern and NgRx Implement a RESTful APIs using Node.js, Express.js, and MongoDB Create secure and efficient web apps for any cloud provider or your own servers Deploy your app on highly available cloud infrastructure using DevOps, CircleCI, and AWS Who this book is for This book is for developers who want to confidently deliver high-quality and production-grade Angular apps from design to deployment. Developers that have prior experie ...